Roland Barthes Semiotics Analysis in Tokopedia Advertising Ramadhan Special - Kezia Nafiry; Sheryn Wijaya; Zakiah Nuril Safiirah (LPPM Stikosa - AWS, 2022)
COVID-19 pandemic that hit the world, including Indonesia, gave a huge impact on many factors, especially the mobility of people, in carrying out their daily activities. To help this problem, Tokopedia which is one of the biggest e-commerce in Indonesia communicated special advertising activities throughout Ramadan with the slogan “Dekatkan yang Jauh, Kirim yang Bermakna''. The ads are very interesting, because it describes the condition of recent society or situation in the pandemic COVID-19, so the authors do a semiotics approach to dissect the meaning of the signs displayed in the advertisement in from plot, facial expressions, gestures, and backgrounds by using Roland Barthes' semiotic approach to dissect the meaning of the signs displayed in advertisements in connotation, denotation, and myth. The conclusion from analysis shows that Tokopedia wants to create a myth that 'far' has different meanings depending on how someone responds to it, besides that Tokopedia also wants to convey the message that no matter how far the distance that is the limit during the pandemic period can be reached by Tokopedia. Through the research made, it can be seen that the role of plot, facial expressions, gestures, and background in an advertisement is very important in conveying messages to the public so that it needs to be displayed properly.